PENERAPAN METODE MUROJA’AH DALAM MENINGKATKAN HAFALAN AL-QUR’AN DI PESANTREN UKHUWAH MUSLIMIN GOWA - Mukarramah, Sitti; Mustamin; Ahmad; Bunyamin, Andi; Azhar, Muh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the application of the muroja'ah method and to determine the improvement of students' memorization of the Qur'an through the application of the muroja'ah method in the Al-Qur'an Hadith subject of class VIII.1 at the Ukhuwah Muslimin Islamic Boarding School in Gowa. This study uses the Classroom Action Research (CAR) type with the Kemmis and McTaggart model consisting of four stages, namely planning, action implementation, observation, and reflection. The study was conducted in two cycles beginning with the pre-cycle stage. The research subjects were 35 students of class VIII.1. Data collection techniques included observation, memorization tests, interviews, and documentation. Data were analyzed using descriptive analysis through the calculation of average scores and percentage of learning completion. The results of the study indicate that the application of the muroja'ah method is able to improve students' memorization of the Qur'an. In the pre-cycle, only 12 students (34.28%) achieved completion with an average ability that was still low. After the implementation of the muroja'ah method in cycle I, the number of students who achieved completeness increased to 24 people (68.57%), although the success indicator had not been achieved so the research was continued to cycle II. In cycle II, there was a more optimal increase, namely 30 students (85.71%) achieved completeness with an average score of 84.57. In addition to improving memorization results, the implementation of the muroja'ah method also increased the activity, concentration, motivation, and self-confidence of students during the learning process. Based on the results of the study, it can be concluded that the implementation of the muraja'ah method is effective in improving the memorization of the Qur'an of class VIII.1 students in the Al-Qur'an Hadith subject at the Ukhuwah Muslimin Islamic Boarding School in Gowa. This method can be used as an alternative learning method to improve the quality of students' memorization of the Qur'an in a sustainable manner.